Screen printed carbon CsPbBr3 solar cells with high open-circuit photovoltage - Jenny Baker (Journal of Materials Chemistry A, 2018)
Screen printed mesoporous carbon solar cells (mC-PSC) are a promising fully printable technology that does not require organic hole conductors, expensive metal contacts or vacuum processing. However, when infiltrated with the archetypal CH3NH3PbI3 perovskite, mC-PSCs show low voltage which limits their use in innovative applications such as indoor light harvesting. Here we investigate both planar (C-PSC) and mesoporous (mC-PSC) carbon cells, based on all-inorganic CsPbBr3. Pure CsPbBr3 is a yellow material with an orthorhombic crystal structure at room temperature and a 2.3 eV band gap, which is not ideal for solar cell applications. However, CsPbBr3 is thermally stable up to over 400 °C and high-voltage planar carbon solar cells, with open circuit voltages of up to 1.29 V and efficiencies up to 6.7% have been reported in the literature. We focus on the effect of the post-annealing temperature on the material properties and photovoltaic activity. XPS and XRD results show a non-linear trend with temperature, with significant improvements in composition between 200 and 300 °C. Both the mesoporous and planar champion devices were obtained after heat processing at 400 °C, reaching PCEs of 8.2% and 5.7% respectively. The average Voc for the planar and mesoporous devices were 1.33 V and 1.27 V respectively with a record 1.44 V for the best mC-PSC.